(untitled) (Mustansiria Dental Journal, 2018)
Thalassemia major is no longer a disease of childhood. Life expectancy of these patients has increased as a result of the dramatic change in medical management of thalassemia major in the past two decades. As patients with thalassemia major become older, their needs also are changed. Patients now face new issues, such as having families, obtaining higher education, and securing employment, which need more care and attention for their appearance in general and dental health in special. The aim of this study was to compare the dental maturity and integrity of a group of patients with β thalassaemia major with age and sex matched healthy controls in Baghdad. For this cross sectional study, a convenient sample of 100 (72 males and 28 females) thalassemic patients who were attending the thalassemia centers in AL-Karama and Ebin-AL Balady hospital was involved. The age of the patients ranged from 6 to15 years. A similar number, of healthy individuals matching with age and gender, was selected as control. Plaque, calculus, and gingival indices as well as decayed, missed and filled surfaces indicator are significantly different in thalaessaemic patients in comparison to control group. The thalaessaemic patients also demonstrated a delay in the development of their dentition. The thalassemic patients demonstrated a delay in the development of their dentition. The mean difference between chronologic and dental age was found to be statistically significant